Is stress always bad? : A critical review on stress that promotes resilience and positive outcomes - Angka, Christy (2019)
This paper explores the field of research on moderate stress and its impact on future outcomes, specifically with the development of resilience against future adversities as an underlying mechanism. While general research on stress agrees that chronic life stress leads to poorer later overall functioning, a growing number of research has found that moderate stress that triggers one’s coping mechanisms without exhausting existing resources fosters resilience growth after one successfully resolves the challenging event. Possessing sufficient initial coping resources and knowledge on how to utilize them prior to stressful events could also increase one’s potential to overcome future stressors, develop greater coping capacity and enjoy more positive outcomes in other life domains. Resilience has been broadly discussed as an underlying mechanism between exposure to moderate stress and positive outcome in the existing literature though researchers have defined, operationalized and measured it in different ways. This paper thus aims to review existing literature to consolidate research methods and findings, and discuss the strengths and weaknesses of such research that should be considered when replicating similar studies in local context. The discussions made in this paper would contribute to future research directions.